Prospective teachers’ beliefs on mathematics during internships—a quasi-longitudinal analysis - Woltron, Felix; Götz, Stefan (Frontiers in Education, 2025)
Prospective teachers repeatedly emphasize the importance of practical phases during mathematics teacher education. Therefore, in light of the professionalization of teacher education, prospective teachers’ beliefs during their internships are examined within a (quasi-)longitudinal study. The purpose of this study is to evaluate key points and desiderata to get a deeper insight into the landscape of prospective teachers’ beliefs. The gathered results could be considered in the development of a theoretical framework for supporting courses related to the practical phases. Based on the results of this study, certain categories identified in the TEDS-M study could be confirmed. Moreover, the beliefs concerning the sub-categories of those categories do not change significantly during the practical phases. This stability is also expressed by the result that a dynamic view on mathematics, a constructivist focus on teaching mathematics and a self-active understanding of once own given lessons dominate a static view on mathematics, a transmissive focus on teaching mathematics and a traditional directive understanding of self-conducted teaching Finally, significant correlations between subcategories could be evaluated. Using the obtained results, a draft of a didactically based design supporting the practical phases is formulated.